TRADISI NYADRAN (RUWAHAN) SEMARAK MENYAMBUT RAMADAN DI DUSUN JALAN DAN JONGGRANGAN DESA BANARAN KAPANEWON GALUR - Ina Aryanti; Akbar Al Masjid (Haluan Sastra Budaya, 2023)
Indonesia is a country with a lot of diversity such as diversity in religion, customs, ethnicity, nation, language, culture, etc. The Nyadran tradition is one of the traditions that exist in Indonesia which is still implemented and preserved in several regions in Indonesia. One area that still implements and preserves this tradition is Jalan Jonggrangan hamlet, Banaran, Galur, Kulon Progo. The Nyadran tradition which is the result of acculturation of Javanese, Hindu, Budhist, and Islamic culture has a procession, uborampe, and the values contained it. Cultural and educational values can be learned and applied in everyday life in society. This study aims to describe the Nyadran tradition in the procession, uborampe, and the values contained in it. The method used in this study is a qualitative method. The data collection technique used in this research is a field research technique with observations, recording the observed, study objects, interviews, and literature review.